The Concept of Freedom in The Context of Iraqi-Kurdistan's High Schools Curriculum- (Literature Subject and) Kurdish Language as A Sample: (An Analytical and Psychological, Educational Study) - Mohammed, Nasraddin I. (Humanities Journal of University of Zakho, 2019)
The research aims to figure out and identify the level of frequency and existence of the concept of freedom in the Literature subject and Kurdish language in the context of high school stage among Iraqi-Kurdistan's curriculum, and for this purpose the researcher prepared a list of kinds of freedom, after distributing it on the experts and extracting the psychometric properties, and for the purpose of processing data was used appropriated the researcher used the statistical descriptive analytical methods, through a sample contains (748) pages from (845) pages, or (89 results shows that the concept of freedom (1673) times has been repeated in this program, and there is a meaningful statistical differences at (0.05) in the existence and frequency of freedom's concept in the sample according to (study stage, class and kind of freedom) for the concept of freedom within the mentioned curriculum. variables.